Crop Yields in European Agroforestry Systems: A Meta-Analysis - Ivezić, Vladimir; Yu, Yang; Werf, Wopke van der (Frontiers in Sustainable Food Systems, 2021)
Agroforestry combines the production of tree and crop outputs with the provisioning of ecological services, such as carbon sequestration, recycling of nutrients, microclimate mitigation and erosion control. Adoption of agroforestry by farmers depends on economic outcomes, which are strongly related to crop yields. Information on yields is scattered in the literature and a quantitative overview of crop yields in European agroforestry systems is lacking. We therefore synthesized published information on crop yields in European agroforestry systems, using meta-analysis. Relative crop yields in modern alley cropping systems (systems with tree rows with interspersed crop strips) were 96% of sole crop yield at tree planting, decreasing with 2.6% per year over the first 13 years of the tree stand, indicating increasing competitive effects of the growing trees on crop yields. On the other hand, studies in traditional Dehesa and Montado systems in Southern Europe showed no difference in crop yield between sole crops and mixtures with trees, indicating that competition between crops and trees plays a less important role in those systems than in alley cropping. Nevertheless, crop yields decreased with tree density and increased with greater distance from the trees in both alley cropping and Dehesa. Overall, the study showed a need for more experimental data to substantiate the benefits of agroforestry and elucidate optimal agroforestry practices under European conditions.